Compensatory Changes in the Anterior Segment and Vascular System of the Eye in Myopic Children After Orthokeratology - Yanwei Chen; Xi Shen (Frontiers Media S.A., 2021)
Purpose: To analyze changes in the anterior segment, retinal vessel density, and choroidal thickness (ChT) after orthokeratology (Ortho-K).Methods: Myopic children were enrolled from Ruijin Hospital, Shanghai, China. Ortho-K lenses and single-vision spectacles were fitted for myopia correction. Ocular measurements were taken at baseline and 6 months, including axial length (AL), central corneal thickness (CCT), anterior chamber depth (ACD), lens thickness (LT), white to white (WTW), ChT, macular vessel density (MVD), and optic disc vessel density (OVD).Results: Seventy-six patients were enrolled in this study, including 40 in the Ortho-K group and 36 in the control group. At baseline, no parameters between the two groups were statistically different. After 6 months, changes in CCT and ACD decreased in the Ortho-K group compared with those in the control group (p < 0.05); LT and ChT in the Ortho-K group were thicker than those in the control group (p < 0.05), while there was no difference in MVD and OVD compared with those in the control group (p > 0.05). There were moderate positive correlations between ChT and LT and between ChT and OVD in the Ortho-K group (p < 0.05).Conclusion: The changes in the anterior and posterior segments of the eye after Ortho-K lens wearing suggest that the human eye has a powerful compensatory effect on the imposed defocus.